Evaluation of the retinal vascular calibres and its associated factors in children with type 1 diabetes mellitus - Bari, Muhd Syafi Abd (2021)
Background: Poor glycaemic control in patients with type 1 diabetes mellitus (Type 1 DM) is closely associated with an increased risk of microvascular complications. Our study aims to determine the mean retinal arteriolar and venular calibres between the good and poor glycaemic control at baseline visit, mid visit and last visit. We also look into the co-factors associated with the retinal vascular calibres in children with type 1 DM. Methods: A cross-sectional prospective hospital-based study involving children with Type 1 DM. The participants were recruited from Ophthalmology and Paediatric Clinics of Universiti Sains Malaysia Hospital. Fundus photo of right eye were taken at baseline, mid and final visit and analysed by Singapore 1 Vessels Analysis (SIVA). HbA1c at each visit were documented. Main Outcome Measure: Mean central arteriolar equivalent (CRAE) and venular equivalent (CRVE) in good and poor glycaemic control were determined at each visit and its associated factors were analysed. Results: The mean presenting age were 12.5 (2.24) years old. Majority of the participants were Malay race and mostly had poor glycaemic control. The mean CRAE and CRVE were not significantly differ for both group at each visit. However, the mean CRVE were significantly wider (p=0.037) in poor glycaemic control along the duration of follow up. Age, duration of DM, blood pressure, BMI and HbA1c are not associated with vascular calibres. Conclusion: A wider CRVE is associated with poorly glycaemic control DM. It can be one of earlier indicator in detecting the progression to diabetic retinopathy. In this closer and shorter duration of follow up study, no significant associated factors between age, duration, blood pressure, BMI and glycaemic control with retinal vascular calibres.